Strengthening The Competence of Halal Slaughter Through Kang Jalal Training by The Nahdlatul Ulama Mosque Management Council Central Lampung - Ismail, Habib; Rahmawati, Rita; Rini, Etika; Aripin, Khairul (TAAWUN, 2025)
This program aims to enhance butcher competency through halal slaughter training based on Islamic principles. The “Kang Jalal” training was conducted by the Nahdlatul Ulama Mosque Management Board (LTMNU) of Central Lampung, using methods such as education sessions, hands-on training, mentoring, evaluation, and direct field application. A total of 228 participants from eight sub-districts and one city took part in the program. The training materials covered theoretical aspects of slaughtering fiqh, technical cutting procedures, and ethical slaughter practices. Results showed a significant improvement in participants’ understanding and skills, along with a growing awareness of the importance of halal certification. This training has had a positive impact in shaping professional, religiously observant, and ethical butchers, while also strengthening the role of the mosque in empowering the community. The program has provided tangible benefits to the community by developing competent and ethical slaughterers and reinforcing the mosque's role as a center of community empowerment and the development of a sustainable halal ecosystem.